2013
DOI: 10.2106/jbjs.l.10005
|View full text |Cite
|
Sign up to set email alerts
|

Early Follow-up of Reverse Total Shoulder Arthroplasty in Patients Sixty Years of Age or Younger

Abstract: RSA as a reconstructive procedure improved function at the time of short-term follow-up in our young patients with glenohumeral arthritis and rotator cuff deficiency. Objective outcomes in our patient cohort were similar to those in previously reported studies. However, overall satisfaction was much lower in this patient population (81%) compared with that in the older patient population as reported in the literature (90% to 96%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(85 citation statements)
references
References 26 publications
7
77
1
Order By: Relevance
“…The mean prevalence of scapular notching was 35 %, which is similar to the percentages reported in several studies [13,31,33,34] in which the rate ranged from 43 to 51 %, and lower than the 68 % found by Boileau et al [9]. As in other studies [30,33], the notching did not appear to affect the clinical outcome.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The mean prevalence of scapular notching was 35 %, which is similar to the percentages reported in several studies [13,31,33,34] in which the rate ranged from 43 to 51 %, and lower than the 68 % found by Boileau et al [9]. As in other studies [30,33], the notching did not appear to affect the clinical outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Of the 45 patients of this review for whom the subjective outcome of surgery was reported [42,44,46], 77 % considered their results as excellent or good. This rate is comparable to that obtained recorded in several studies in which the RSA was mostly implanted for massive cuff tears or CTA [10,13,31,51].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, studies have demonstrated a high rate of radiolucency about the glenoid component [ 56 ], which may translate into a higher risk for failure and need for revision in these young patients. Given its functional limitations, reverse total shoulder replacement has generally not been considered an option for young patients; furthermore, recent evidence suggests a lower satisfaction rate [ 65 ] and higher complication rate [ 66 ] in this patient demographic, and the long-term survivability has yet to be determined.…”
Section: Shouldermentioning
confidence: 99%
“…Yet long-term studies have shown declining functional outcome scores with time, a high risk of complications, and a lower likelihood of satisfaction in young patients [2,3,13]. As an alternative, hemiarthroplasty can be considered for patients with painful CTA without instability and for whom conservative treatment has failed.…”
Section: Introductionmentioning
confidence: 99%